Les moyens stratégiques pour prendre la parole en français et en slovene - Zwitter Vitez, Ana (Vestnik za tuje jezike, 2014)
The main challenge of the contribution was to identify the most effective strategic structures when two speakers want to speak at the same time. We reviewed state-of-the-art studies for French and analyzed three spontaneous conversations in Slovene from prosodic, morphosyntactic and discourse perspective. The results show that speakers who were efficient in taking their turn produced many pauses, repetitions and auto-corrections as well as longer discourse preambles than the speakers who were less successful in taking (or keeping) their turns.
Keywords: francoščina; French; Slovene; slovenščina; govorjeni jezik; spontani govor; prevzemanje besede; strateška sredstva; pragmatika